REKA JENIS KELAMIN ANAK DALAM PERSPEKTIF SAINS DAN ISLAM - Anip Dwi Saputro (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
Considering each cell between the reproductive cells contains half of the amount contained in the body cell and assigned to him, the existence of post-law partner is one sign of the greatness of God in creating his creatures. This is due to the merging of both male and female reproductive cells to form the zygote, then fulfilled the specified number of chromosomes to the human species, creating diversity in character between both parents and children are increasingly enrich life and make it more alive. This diversity also provedthe power of God designed such a process that occurs in the zygote when it was out of humans, animals, plants as new creatures like its predecessor in several different characters and in some other characters. In humans, each body cell contains 46 chromosomes, arranged in 23 pairs that are similar in terms of shape, but different in terms of structure and gene carried by each chromosome. The amount of raw character (fixed) in the cells of male and female, although there are differences in the chromosomes for specified sex.Male body cell contains 44 chromosomes, plus two chromosomes of sex which are not similar, because one of them labeled masculine (Y), and the other is labeled feminine (X). With the same composition, a woman's body cells contain 44 chromosomes, in addition to the two chromosomes of sex, but both of them are feminism (X, X).With this process, each human character has a pair of genes, one derived from the father and predecessor, while the other comes from the mother and predecessor. Gen stronger will dominate, and the character of this gene is hereinafter referred to as the dominant character. Being weaker genes will disappear and step aside for a while to appear again later in the next generation. Therefore, the character brought termed recessive character. Thus, the character of the child may be different from the character of his brothers, or parents or predecessors.